A Comprehensive Literature Review of Physician Posttraumatic Stress Disorder During COVID-19 - Stefanus, Stefanus; Vanessa, Vanessa (The International Journal of Medical Science and Health Research, 2024)
Background: The literature review highlights the significant psychological impact of the COVID-19 pandemic on healthcare professionals, particularly concerning the prevalence of post-traumatic stress disorder (PTSD). The initial studies, such as the one by (A. Marco et al., 2020), revealed that emergency physicians reported PTSD symptoms, with identified stressors including disinformation and workload. This early finding set the groundwork for subsequent research, which consistently indicated that high-stress environments and inadequate resources contribute to the risk of PTSD among healthcare workers ((d’Ettorre et al., 2020); (Batra et al., 2020)). Literature Review: As the pandemic unfolded, studies demonstrated that healthcare professionals faced compounded psychological burdens, with factors such as long working hours and emotional exhaustion exacerbating their vulnerability to PTSD ((Luiz Carvalho Braule Pinto et al., 2021); (Chang et al., 2022)). The findings from (Sun et al., 2021) emphasized the alarming prevalence of PTSD symptoms and the lack of targeted interventions for healthcare providers, indicating a critical gap in the existing literature. Furthermore, the emotional toll of the pandemic was linked to increased anxiety and psychological distress, underscoring the need for ongoing research and support systems to address these issues ((De Pasquale et al., 2022)). Conclusion: Collectively, the studies reviewed indicate a concerning trend regarding the mental health of healthcare professionals during the COVID-19 pandemic, with PTSD emerging as a significant issue that requires urgent attention. The evidence points to the necessity for systematic assessments, targeted interventions, and robust support systems to address the mental health challenges faced by this critical workforce, particularly as the long-term consequences of untreated PTSD could adversely affect both healthcare providers and patient care.